STEM-based Pure Water Kit: Enhancing science process skills and environmental awareness in support of SDGs - Rahmah, Nafisah Maulidah; Susantini, Endang; Majid , Dewi Firta Amalia; Suaidah, Husfina Lailiyatus; Rukmana, Rinaldiyanti (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2026)
Science process skills (SPS) and environmental awareness are essential 21st-century competencies that remain insufficiently developed among high school students in Indonesia. This study aimed to analyse the improvement of students' SPS following STEM-based learning using the Pure Water Kit on the topic of environmental pollution, and describe students' environmental awareness after the learning process. A one-group pretest–posttest design was employed with 36 tenth-grade students at SMAN 1 Krian, Sidoarjo, selected through purposive sampling. Three instruments were used: a five-item SPS test (Cronbach's α = 0.74; highly valid, ā = 3.8/4.0), a STEM-based Student Worksheet, and a nine-item Guttman-scale environmental awareness questionnaire (α = 0.81; highly valid, ā = 3.6/4.0). The Pure Water Kit was validated by three experts (mean score = 3.8/4.0; highly valid). Results showed that the mean pretest score of 73.95 increased to 93.64 on the posttest (N-Gain = 0.82; high category). The Wilcoxon signed-rank test confirmed statistical significance (Z = −5.257, p < 0.001; Cohen’s d = 2.43). Post-intervention, environmental awareness reached 96.3% (very high category). These findings indicate that the STEM-based Pure Water Kit effectively enhances SPS and environmental awareness in a single-group classroom setting. Finally, the findings have implications for SDG 4 (Quality Education) and SDG 6 (Clean Water and Sanitation) but should not be generalised beyond this specific context.